Hubungan Kompetensi Sumber Daya Manusia Terhadap Kinerja Karyawan Pada PT. Perkebunan Nusantara I Regional 8 Unit Kebun Awaya Di Desa Liang Kecamatan Teluk Elpaputih Kabupaten Maluku Tengah - Sahetapy, Marsel; Sopamena, Junianita F; Lawalata, Marfin (Universitas Pattimura, 2025)
The Relationship of Human Resource Competence to Employee Performance at Pt. Perkebunan Nusantara 1 Regional 8 Awaya Plantation Units in Liang Village, Teluk Elpaputih District, Central Maluku Regency. This study aims to determine the relationship between human resource competence and employee performance of PT. Nusantara I Regional Plantation 8 Units of Awaya Plantation, Liang Village, Teluk Elpaputih District, Central Maluku Regency. The method used in this study is a random sampling technique because the population is relatively homogeneous. The results of the study show that human resource competence has a positive and significant influence on employee performance at PT Perkebunan Nusantara 1 Regional 8 Units Kebun Awaya.